Halal Food Preferences and Perceptions at Nagoya Mall Batam - Yusuf Faisal; Ida Busneti; Egi Gumala Sari (IAIN Syekh Nurjati Cirebon, 2022)
The purpose of this study was to see the preferences and perceptions of halal food at Nagoya Mall in Batam City. This research was conducted at the Nagoya mall which provides halal food in the food street area. The samples of this research are lecturers at 4 universities in Batam which are managed by Persyarikatan Muhammadiyah and Hidayatullah namely: Muhammadiyah International Tarbiyah College, STIKOM Muhammadiyah Batam, Abdullah Said Islamic Institute, and Hidayatullah Tarbiyah Science College. In this study, it was found that the preferences and perceptions of lecturers about halal food stands in Nagoya tended to be good with a note that there were several things that were improved including cleanliness